Spontaneous bilateral chylothorax in both vena cava thrombosis; cisterna chyli ligation - Bayrakci, Onur; Borazan, Ersin; Şanli, Maruf; Yagci, Sevinç; Kusdogan, Nurevşan (International Surgery Journal, 2021)
Chilothorax, a rare clinical condition characterized by high triglyceride white fluid in the thoracic cavity; when the literature is examined, it is seen because of trauma, malignancy, complication of surgery, and rarely central catheter-related thromboplasty. In the treatment, diet change, nutrition, drainage with tube thoracostomy, conservative method, surgical procedure with thoracotomy are applied.In our case there was no response to nutritional changes, drainage, thoracotomy and somatostatin treatments. Cisterna chyli ligation was performed with laparotomy. We present a case of spontaneous bilateral chylothorax associated with superior and inferior vena cava thrombosis (without central catheter relationship).